2019
DOI: 10.3390/app9020306
|View full text |Cite
|
Sign up to set email alerts
|

Model-Free Identification of Nonlinear Restoring Force with Modified Observation Equation

Abstract: Nonlinearity exists widely in civil engineering structures; for example, the initiation and growth of damage under dynamic loadings is a typical nonlinear process. To date, for the purpose of structural evaluation and a better understanding nonlinear characteristics of complicated structures, a number of parametric and nonparametric methods have been developed for the identification of nonlinear restoring force (NRF). However, due to the highly individualistic nature of nonlinear systems, it would be inefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, in some practical situations, for example an earthquake-excited building, the measurements of loadings are sometimes unavailable. Therefore, the parameters cannot be directly identified according to Equation (8) in this case. Additional information or supplementary equations are required for the identification.…”
Section: Proposed Iterative Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some practical situations, for example an earthquake-excited building, the measurements of loadings are sometimes unavailable. Therefore, the parameters cannot be directly identified according to Equation (8) in this case. Additional information or supplementary equations are required for the identification.…”
Section: Proposed Iterative Identification Methodsmentioning
confidence: 99%
“…To date, a number of vibration-based system identification and damage detection methods have been developed, and review articles with different emphases can be also found [2][3][4]. In general, structural parameters identification can be performed in three different paradigms: (i) time domain (e.g., [5][6][7][8][9][10]), (ii) frequency domain (e.g., [11][12][13][14]), and (iii) time-frequency domain (e.g., [15][16][17]).…”
Section: Literature Surveymentioning
confidence: 99%
“…In the nonlinear behavior identification approaches proposed in the above studies, a parametric mathematical model describing the nonlinear behavior of the structure to be identified should be assumed in advance. Considering the complexity and individuality of structural nonlinear behavior of engineering structures in practice that are made of different construction materials with different structure types, the development of nonparametric or mathematical model‐free identification methods for nonlinear systems has received significant attention and has shown their advantages in recent years 3,4,39,40 . A new technique called “Describing Surface Method” (DSM) was developed by Karaagacli and Ozguven 41 to identify local nonlinearity in a dynamic structure in an nonparametric way.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complexity and individuality of structural nonlinear behavior of engineering structures in practice that are made of different construction materials with different structure types, the development of nonparametric or mathematical model-free identification methods for nonlinear systems has received significant attention and has shown their advantages in recent years. 3,4,39,40 A new technique called "Describing Surface Method" (DSM) was developed by Karaagacli and Ozguven 41 to identify local nonlinearity in a dynamic structure in an nonparametric way. However, this method requires measuring the complete dynamic responses at each DOF of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the flexural testing of high-performance steel beams, steel bar corrosion [26], testing of bonding behavior in reinforced concrete [27], among others [28,29]. At a higher level, using the current understanding of system mechanical behaviors, investigators have developed methods to identify, extract features, and classify the health of different structures using minimal knowledge of system behavior [30][31][32][33][34][35]. Supporting such work are other researchers that specialize in the long-term monitoring of damage and help strategize everything from sensor placement to understanding what the key parameters that need to be monitored are.…”
mentioning
confidence: 99%